(untitled) (VERUM: Journal of Scientific Initiation, 2026)
The aim of this article is to comparatively analyze the flexibility strategies adopted in three Social Housing case studies in order to identify the most effective typological and construction solutions. The methodology employed a case study approach to understand contemporary phenomena applied within a specific context. The results indicated that flexibility is more evident in evolutionary aspects, such as expandability, and in changes to room occupancy, than in multifunctionality achieved through adaptable elements. The most recurrent criteria were: the possibility of planned expansion, clear spatial zoning, multifunctional/adaptable-use spaces, and the separation of structural and enclosure systems. However, there was insufficient investment in "second-generation" solutions (movable furniture or movable partitions). It is concluded that flexibility should be understood as the project’s ability to accommodate different lifestyles and family life-cycle stages, requiring planned expansion to be incorporated from the design phase.